2021
DOI: 10.1186/s41936-020-00201-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lambda-cyhalothrin oxidative stress and gonad histoarchitecture toxicity potency in Clarias gariepinus

Abstract: Background Extensive and indiscriminate use of pesticides gradually destroys the environment (ecosystem), poses serious threats to human health, animal life (especially aquatic), plant forms, soil, water, and also lead to emergence of resilient species of life forms that are becoming resistant to pesticides. The present study focused on evaluating lambda-cyhalothrin oxidative stress and gonad histoarchitecture toxicity potency in Clarias gariepinus. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Several reports have shown that it is abundantly present in water resources [51][52][53] and it is susceptible to entering the trophic chain [54]. L-CHT is highly toxic to amphipods, aquatic invertebrates, fish, and mice [51,[55][56][57][58][59][60]. Humans exposed to cyhalothrin via ingestion of food, inhalation, dermal contact, or drinking water can be exposed to deleterious and harmful effects [56,61].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that it is abundantly present in water resources [51][52][53] and it is susceptible to entering the trophic chain [54]. L-CHT is highly toxic to amphipods, aquatic invertebrates, fish, and mice [51,[55][56][57][58][59][60]. Humans exposed to cyhalothrin via ingestion of food, inhalation, dermal contact, or drinking water can be exposed to deleterious and harmful effects [56,61].…”
Section: Introductionmentioning
confidence: 99%
“…The alterations in all parameters were significantly dose and time dependent (41). Ezenwosu et al, (2021) investigated the effect of λ-cyhalothrin on oxidative stress in Clarias gariepinus. On the 7th day, CAT activity increased, on the 14th day; It was determined that SOD activity increased and there was a significant increase in all parameters except SOD on the 21st and 28th days (42).…”
Section: Discussionmentioning
confidence: 99%
“…Ezenwosu et al, (2021) investigated the effect of λ-cyhalothrin on oxidative stress in Clarias gariepinus. On the 7th day, CAT activity increased, on the 14th day; It was determined that SOD activity increased and there was a significant increase in all parameters except SOD on the 21st and 28th days (42). Koç and Akçay (2018) investigated the effects of λ-cyhalothrin on Capoeta capoeta (Guldenstaedt 1773) caught from Kars Brook by biochemical and molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity degree depends on its dose, method and duration of exposure. LCT is known as a strong agent for biochemical distortion, nervous disruption and oxidative damage (Ezenwosu et al, 2021;Alrawe and ALzibaidy, 2022). Kandil et al (2022a) reported that LCT bait (0.032 %) has rodenticidal efficacy under laboratory and field conditions against black rats (Rattus rattus).…”
Section: Introductionmentioning
confidence: 99%